2015
DOI: 10.1007/s13199-015-0326-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, richness and degree of colonization of arbuscular mycorrhizal fungi in coconut cultivated along with intercrops in high productive zone of Kerala, India

Abstract: Degree of arbuscular mycorrhizal (AM) association and its diversity were investigated in the coconut palm (Cocos nucifera L.) cultivated in crop mixed system under rain-fed condition in a highly productive humid tropical zone in Malappuram district of Kerala, India. Forty AM species belonging to ten genera viz. Acaulospora, Claroideoglomus, Dentiscutata, Diversispora, Funneliformis, Gigaspora, Glomus, Redeckera, Scutellospora and Septoglomus were recorded indicating high level of AM richness in coconut rhizosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 72 publications
2
10
0
1
Order By: Relevance
“…All other comparisons were non-significant SDB (g) % col P (g kg -1 ) Babassu dominance (%) 10 0. and Cardoso 2006), and similar to those found in an alley cropping system located 20 km from our study site (148 to 335 glomerospores in 100 g of soil) (Nobre et al 2010). Our values for mycorrhizal colonization rates of babassu roots and MIP were in line with values reported for a peach-palm culture in the Amazon (13.54 -43.95%) (Silva Júnior and Cardoso 2006) and coconut plantations in India (32.33 -55.17%) (Rajeshkumar et al 2015). Our MIP values were also similar to those reported by Nobre et al (2010) in a legume alleycropping system (51to 54%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All other comparisons were non-significant SDB (g) % col P (g kg -1 ) Babassu dominance (%) 10 0. and Cardoso 2006), and similar to those found in an alley cropping system located 20 km from our study site (148 to 335 glomerospores in 100 g of soil) (Nobre et al 2010). Our values for mycorrhizal colonization rates of babassu roots and MIP were in line with values reported for a peach-palm culture in the Amazon (13.54 -43.95%) (Silva Júnior and Cardoso 2006) and coconut plantations in India (32.33 -55.17%) (Rajeshkumar et al 2015). Our MIP values were also similar to those reported by Nobre et al (2010) in a legume alleycropping system (51to 54%).…”
Section: Discussionsupporting
confidence: 90%
“…Total glomerospore abundances found in this study were lower than those reported for mycorrhizal associations of Desmoncus orthacanthos Mart. in Mexico (400 to 3200 glomerospores per 100 g of soil) (Ramos-Zapata et al 2006), and in a coconut plantation in Kerala, India (214 to 299 glomerospores per 50g of soil) (Rajeshkumar et al 2015), higher than in a peach-palm (Bactris gasipaes Kunth) rhizosphere in the Amazon (27 to 48 glomerospores in 50 g of soil) (Silva Júnior Table 4. Mycorrhizal infection potential (MIP) with sorghum as trap plant in soil from two environments in the eastern Brazilian Amazon: secondary forest fallow regrowth sites with different babassu dominance, and pasture at different distances from babassu patches.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of a negative correlation between AM fungal colonization and soil pH is in agreement with other studies in which such a relationship was found in coconut, potato and medicinal plants (Das & Kayang 2010;Rajeshkumar et al 2015;Wang & Jiang 2015). A number of soil and fungal factors are affected by soil pH.…”
Section: Discussionsupporting
confidence: 93%
“…Although soils with EC less than 1 dS/m are considered to be nonsaline and do not affect microbial processes, soil EC in the range of 0.028-0.270 dS/m is reported to negatively influence AM fungal colonization (Halder et al 2015;Wang & Jiang 2015). However, Rajeshkumar et al (2015) reported a significant positive correlation between soil EC and root length colonized by AM fungi in coconut growing in soils having an EC range of 0.018-0.122 dS/m. As inherent soil and climatic factors modulate the effect of EC on biological processes, the divergent results on the influence of EC on AM fungal colonization in these studies are tenable.…”
Section: Discussionmentioning
confidence: 99%
“…Spore movement over longer distances is more stochastic and may be unreliable for adequate inoculation levels (Peay et al, 2012). Dominated by monocots such as grasses and coconut palms, which are endo-(arbuscular)-mycorrhizal (Brundrett, 2009;Rajeshkumar et al, 2015), the baseline land use prior to plantation establishment in our study would have little capacity to support ECM fungi. As such, we speculate that dispersal of ECM fungi into plantation sites is necessary but restricted and limits the capacity for complete soil microbial restoration if tree planting is not accompanied by ECM inoculation of plantation seedlings (Aggangan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%